Case report: Cystic hygroma accompanied with campomelic dysplasia in the first trimester caused by haploinsufficiency with SOX9 deletion - Liu, Xijing; Wang, Jianmin; Yang, Mei; Tian, Tian; Hu, Ting (Frontiers in Genetics, 2022)
Introduction: Campomelic dysplasia (CD) is a rare autosomal dominant skeletal malformation syndrome characterized by shortness and bowing of the lower extremities with or without XY sex reversal. Diagnosis using ultrasonography is most often made in the latter half of pregnancy. Intragenic heterozygous mutations in SOX9 are responsible for most cases of CD. CD caused by a SOX9 deletion is a rare condition. Case presentation: We present a single case report of an individual with cystic hygroma accompanied by CD, which was detected by ultrasound in the first trimester. Chromosomal microarray analysis (CMA) was performed to determine copy number variants, whereas whole exome sequencing (WES) was performed to elucidate single nucleotide variants. Chorionic villus sampling was performed to enable such analyses. Ultimately, CMA detected a 606 kb deletion in the 17q24.3 region with only one protein-coding gene (SOX9). However, no mutation in the SOX9 protein-coding sequence was detected by WES. Conclusion: When cystic hygroma is detected, prenatal diagnoses by ultrasound for skeletal dysplasia are likely to be confirmed in the first trimester. We propose a comprehensive prenatal diagnostic strategy that combines CMA and WES to diagnose fetuses with cystic hygroma accompanied by skeletal dysplasia.